Escola e paradigmas de gestão - Miguel Henrique Russo (EccoS – Revista Científica)
The text talks about the ongoing paradigmatic transition based uponschool administration theory. Until 80s decade the dominant referenceparadigm for school management was the organizational paradigm, which issuffering, since that, competition from ideas by which the school specificityrequires an administrative theory build up in accordance with the schoolpedagogical production process nature. Contributions to consolidate the newparadigm have its origins in researches with a critical orientation facing themodel of school bureaucratic organization. The text main goal is to introducethis basic question from the school administration theory thematic without theintention of exhausting it.